1981
DOI: 10.1002/1097-0142(19810601)47:11<2678::aid-cncr2820471126>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumors of the pleura: Eight new cases and review of 360 cases in the literature

Abstract: Three-hundred-sixty cases of solitary fibrous tumor of the pleura from the literature are analyzed, and eight new cases are described. Of patients reported on prior to 1972, 72% had symptoms due to the tumor at the time of diagnosis, but only 54% of patients reported on since then were symptomatic. This probably reflects earlier diagnosis as a result of increased use of chest radiographs in asymptomatic populations. Cough, chest pain, dyspnea, and/or pulmonary osteoarthropathy are each found in at least one-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
407
1
70

Year Published

1986
1986
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 669 publications
(487 citation statements)
references
References 62 publications
9
407
1
70
Order By: Relevance
“…19 However, older series also found higher metastatic rates in hemangiopericytoma and pleural solitary fibrous tumor-from 18 to 50%. 2,3,16,20 This variability may be due in part to differences in follow-up time as well as referral bias. Adequate follow-up time is required to determine metastatic frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 However, older series also found higher metastatic rates in hemangiopericytoma and pleural solitary fibrous tumor-from 18 to 50%. 2,3,16,20 This variability may be due in part to differences in follow-up time as well as referral bias. Adequate follow-up time is required to determine metastatic frequency.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7]10,18,[20][21][22] This may be due to the large number of intra-abdominal tumors in our cohort. Previous studies have suggested that tumor size 410 cm is predictive of poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical reports indicate a good prognosis after treatment. Surgical resection cures~90% of these patients, but recurrent disease occurs in the remaining 10% [5].…”
Section: Discussionmentioning
confidence: 99%
“…Solitary fibrous tumors in pleura, peritoneum and other nonvisceral soft tissue are known to present with painless masses and affect older persons between the fourth and seventh decades of life (Goodlad & Fletcher 1991;Young et al 1990;Briselli et al 1981;England et al 1989). Solitary fibrous tumors are usually benign, rarely recur locally with invasion of adjacent tissues and rarely metastasize.…”
Section: Discussionmentioning
confidence: 99%
“…Solitary fibrous tumors with these aggressive features may manifest with invasion of adjacent tissue, recurrence or distant metastases (England et al 1989). Solitary fibrous tumors of the pleura are known to be responsible for patient death in 12% of the cases because of late diagnosis or unresectable recurrence (Briselli et al 1981).…”
Section: Discussionmentioning
confidence: 99%